A review of learning courseware for children with learning disabilities in Malaysia - Suratin, Siti Faridah (ISSI Research Group, 2016)
Children with Learning Disabilities (LD) are different from normal kids. They need special approach in conducting learning sessions. On the other hand, learning courseware is deemed as best way to encourage children with LD to learn. However, there are limited studies reported on the existence of learning coursewares for children with LD in Malaysia. Therefore, this paper aims to identify the presence of LD coursewares in Malaysia and to propose the most effective courseware design for LD children. By using the four-stage method from Bandara.s Systematic Literature Review (SLR), it is found that multimedia application should be considered as the most effective component for developers while designing the learning coursewares for LD. These coursewares provide an interactive education experience for children with LD.